The law of subrogation - Donnelly, Daniel (Trinity College (Dublin, Ireland). School of Law, 2000)
This thesis attempts a thorough review of the law of subrogation as applied in Ireland and England, with reference to the law of other common law jurisdictions and to the views of certain civil law writers. It first introduces the topic and then considers the juridical basis of subrogation. It also attempts to sketch the historical origins and derivation of the modern law of subrogation. Subrogation is generally divided into two categories by civilian and American writers, namely legal subrogation and contractual subrogation. Irish and English courts have not always been careful to make it clear which category they were applying. This has led to considerable confusion and controversy as to the relevance of intention to subrogation. Some authors have laid down the broad proposition that subrogation is a remedy to reverse unjust enrichment and nothing more. This thesis disputes the universal application of the “restitutionary hypothesis.”
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin